On Γ-convergence of integral functionals defined on various weighted Sobolev spaces - Rudakova, O. A. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We consider weighted Sobolev spaces correlated with a sequence of $n$-dimensional domains. We prove a theorem on the choice of a subsequence $Γ$-convergent to an integral functional defined on a “limit” weighted Sobolev space from a sequence of integral functionals defined on the spaces indicated.